2021
DOI: 10.4103/1673-5374.297080
|View full text |Cite
|
Sign up to set email alerts
|

Surgical intervention combined with weight-bearing walking training improves neurological recoveries in 320 patients with clinically complete spinal cord injury: a prospective self-controlled study

Abstract: Although a large number of trials in the SCI field have been conducted, few proven gains have been realized for patients. In the present study, we determined the efficacy of a novel combination treatment involving surgical intervention and long-term weight-bearing walking training in spinal cord injury (SCI) subjects clinically diagnosed as complete or American Spinal Injury Association Impairment Scale (AIS) Class A (AIS-A). A total of 320 clinically complete SCI subjects (271 male and 49 female), aged 16–60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Interestingly, we observed that older age was not associated with worse surgical outcomes in terms of neurological improvement or complication rates 11 . Despite the higher prevalence of tethering in older patients, surgical intervention appeared to be equally effective across age groups, with similar rates of neurological improvement and complication rates observed 12 . This finding contrasts with some previous studies suggesting that older age may be a predictor of poorer surgical outcomes in spinal cord injury patients.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, we observed that older age was not associated with worse surgical outcomes in terms of neurological improvement or complication rates 11 . Despite the higher prevalence of tethering in older patients, surgical intervention appeared to be equally effective across age groups, with similar rates of neurological improvement and complication rates observed 12 . This finding contrasts with some previous studies suggesting that older age may be a predictor of poorer surgical outcomes in spinal cord injury patients.…”
Section: Discussionmentioning
confidence: 83%
“…Upper Extremity With over half of SCI patients suffering from cervical injuries, restoring arm and hand function is essential for daily activities and independence 56 , 57 . For elbow extension, nerve transfers from the teres minor or axillary nerve to the radial nerve’s triceps branch are effective, with the infraspinatus compensating for teres minor sacrifices 28 , 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SCI patients in ICU will definitely halt the early rehabilitation like mobility training with walking aids, which is key to neurologic recovery. 9 The length of hospital stay (LoS-hospital) is another indicator of the occupation of medical resources. 10 However, little attention is paid to the prolonged length of ICU stay (LoS-ICU) or LoS-hospital of the critical SCI patients in ICU.…”
mentioning
confidence: 99%
“…A prolonged stay in an intensive care unit (ICU) will take up a disproportionate amount of medical resources, 8 as it hinders the enrollment of other critical patients. Furthermore, SCI patients in ICU will definitely halt the early rehabilitation like mobility training with walking aids, which is key to neurologic recovery 9 . The length of hospital stay (LoS-hospital) is another indicator of the occupation of medical resources 10 .…”
mentioning
confidence: 99%